Efektifitas Terapi Murottal dan Terapi Musik terhadap Insomnia Mahasiswa Keperawatan Tingkat Akhir di Universitas Indonesia Maju Tahun 2023 - Titin Saputri; Irma Herlina; Hari Ghanesia Istian (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
Insomnia is a sleep disorder experienced by final year students. Therefore, strategies are needed that students can use to reduce the level of insomnia they experience. Murottal therapy and music therapy can be used to reduce insomnia because what results from murottal therapy and music therapy is comfort and calm. The aim of this research is to determine whether or not there is effectiveness of murottal therapy and music therapy on the level of insomnia experienced by final year students at the University Advanced Indonesia. This research uses a Quasi experiment, using the One Group pre and post test design method. The sampling technique used the Pederer formula calculation from a population of 170 to 32 students. This research used the Jakarta Biolois Psychiatric Study-Insomnia Rating Scale (KSPBJ-IRS) questionnaire. The results of this research showed that 27 students (84.4%) experienced mild insomnia, 5 students (15.6%) experienced severe insomnia. After the intervention of murottal therapy and music therapy, 22 students (68.8%) of the 32 students did not experience insomnia and 10 students (31.3%) experienced mild insomnia. The results of the paired sample t-test analysis of murottal therapy show a t value of 4.321 with a significance (Sig) of 0.001. This significance value is far below the significance level of 0.05. for the results of music therapy, it shows a t value of 4.604 with a significance (Sig) of 0.000. This significance value is far below the 0.05 significance level. Therefore, there is a significant difference in results which shows that music therapy is more effective than murottal therapy for treating insomnia in final year nursing students.